2016 ASAHP Annual Conference: Abstracts of the Presentations…Rush University, College of Health Sciences, Imaging Sciences Program: Best Practices in Recruitment and Retention of Diverse Students. - Vasquez, Laura P. (Journal of Allied Health)
Hypothesis: This abstract proposal is to promote best practices in recruitment and retention of diverse students using the Rush University, College of Health Sciences, Imaging Sciences Program as an example. Identifying best practices for recruiting and retaining diverse students is a long-term investment. This program has a rich source of under-represented diverse applicants. The emerging "new student" cohort is the non-traditional, more mature adult who works fulltime, juggles family responsibilities, and balances more competing life roles. Method: The overall strategy of this program is to prepare and support a diverse imaging sciences workforce that is culturally competent. Goals and objectives within the program's strategic plan will be discussed. Observations/Outcomes: Imaging Sciences' Definition of Excellence in Education will be discussed along with the ways to measure excellence. Conclusion: This program is unique in that it works closely w'ith our professional community. Addressing compositional diversity requires proactive institutional support that seeks to develop and maintain a diverse student body. The underrepresentation of minority students in higher education is often viewed as a "pipeline" problem. If we want our diverse student population to continue to flourish, we must be open to explore supportive academic and financial support needs of this student population.